Comparison of Visual Inspection Methods with Pap Smear as Screening Test for Premalignant Lesions of the Cervix - Jyoti Yadav; Shubhra Agarwal; Aayushi Jain (Wolters Kluwer Medknow Publications, 2024)
Aim and Objectives: The present study was done to compare the visual inspection methods with Pap smear as a screening test for premalignant lesions of the cervix. Materials and Methods: The present observational prospective study was done at the Department of Obstetrics and Gynecology at Teerthanker Mahaveer Medical College and Research Center for 18 months. All study subjects were subjected to Papanicolaou smear, VIA, and VILI examination. If any of these tests were found positive, then a colposcopy and cervical biopsy were done. Results: The sensitivity of Pap, VIA, VILI, and colposcopy was 52.63%, 84.21%, 73.68%, and 84.21%, respectively. The specificity of Pap, VIA, VILI, and colposcopy was 60.0%, 80.0%, 60.0%, and 80.0%, respectively. The accuracy of Pap, VIA, VILI, and colposcopy was 54.17%, 83.33%, 70.83%, and 83.33%, respectively. Conclusion: It is well known that VIA and VILI are very easy to carry out and apply. Even technically they do not cost much, consume less tax and can be applied to all the patients. Even the results are calculated in a faster manner which helps in chalking out the plan in an easy way.